Modelling of Biomethane Production from Microalgae - Bashar Zebian; Chakib Bouallou; Silvia Greses; Andriamahefasoa Rajaonison; Paula Pérez-López (Chemical Engineering Transactions)
Microalgae are a prospective feedstock for bioenergy due to their higher productivity, adaptable growing environments, and higher lipid/polysaccharide content compared to terrestrial biomass. Anaerobic digestion is a well-established process that can turn microalgae into biogas and offers a high energy return on investment. The ADM1 model, coupled with a pre-treatment step and a full upgrading processing of the biogas, was implemented. Aspen Plus was the software used to display the process of converting biomass to biomethane through anaerobic digestion and biogas purification techniques in order to determine the mass balance and energy requirements. Simulations were compared to experimental data obtained from University of Almeria, Spain of an anaerobic digester fed with Scenedesmus microalgae. For a 5-ha wastewater open raceway pond and a biomass productivity of 20 g/m2/day, the biomethane had a purity of 94 % using anaerobic digestion accompanied with an enzymatic pre-treatment and amine scrubbing for biogas purification.